ANALISIS METODE TANYA JAWAB TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PPKN DI KELAS RENDAH - Adinda Valerina Tahta; Silfia Yahrotus Salsabila; Yunia Parmastuti; Deni Zein Tarsidi (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the effect of the question-and-answer method on lower-grade students' learning motivation in Civics (PPKn). The question-and-answer method was chosen as the focus of the study because it fosters more active two-way interaction between teachers and students. The study was conducted at an elementary school in Sukoharjo Regency, with third-grade students as subjects. The method used was descriptive qualitative, using observations, interviews, and documentation of the Civics (PPKn) learning. The analysis showed that the question-and-answer method can increase students' learning motivation, as evidenced by increased student engagement in answering questions, asking questions with curiosity, and demonstrating enthusiasm in participating in Civics (PPKn) activities. However, its implementation still faces obstacles, such as some students' shyness or fear of asking or answering questions. Therefore, teachers need to provide positive reinforcement and create a comfortable and safe classroom environment for students. Overall, the implementation of the question-and-answer method has a positive impact on student learning motivation in lower-grade students, especially when supported by appropriate classroom management strategies.